2019
DOI: 10.2174/1871530318666181009112042
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines in Non-functional Adrenal Incidentalomas and Relation with Insulin Resistance Parameters

Abstract: Objective: Adrenal incidentalomas are diagnosed incidentally during radiological screenings and require endocrinological investigations for hormonal activity and malignancy. In certain studies, it has been reported that non-functional incidentalomas can be associated with high adipocytokines levels affecting the insulin resistance just like the adipose tissue with metabolic syndrome. Here, we studied serum adipocytokine levels including leptin, resistin, visfatin, omentin 1 and adiponectin in subjects with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Non-functional adrenal adenoma showed worse endothelial alterations rather than established atherosclerosis (34,35). Akkus reported that nonfunctional adrenal adenoma was associated with increased adipocytokines levels, which affect the insulin resistance and cardiovascular risk factors (36). Our patients with non-functional adrenal adenoma may possibly present in the early stage of inflammation and atherosclerosis, which might be explained why MHR does not associate with non-functional adrenal adenoma.…”
Section: Discussionmentioning
confidence: 65%
“…Non-functional adrenal adenoma showed worse endothelial alterations rather than established atherosclerosis (34,35). Akkus reported that nonfunctional adrenal adenoma was associated with increased adipocytokines levels, which affect the insulin resistance and cardiovascular risk factors (36). Our patients with non-functional adrenal adenoma may possibly present in the early stage of inflammation and atherosclerosis, which might be explained why MHR does not associate with non-functional adrenal adenoma.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, Akkus et al [ 10 ] assessed serum adipocytokine levels, including visfatin, leptin, resistin, omentin 1, and adiponectin in patients with non-functional adrenal incidentalomas (NFAI). These patients demonstrated significantly elevated leptin and resistin levels, as well as significantly decreased adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight or obesity are common conditions accompanying hormonally active as non-functionating adrenal tumors. Adipose tissue works as an endocrine gland secreting adipocytokines such as resistin, leptin, adiponectin, and visfatin, affecting insulin resistance and metabolic syndrome [ 10 , 11 ]. There are not many studies specifying the role and contribution of adipocytokines in the biology of ACC [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Previous studies illustrated that adipocytokine played significant roles in regulation of glucose, lipid and metabolism energy metabolism, which mediated insulin resistance in cardiovascular disease of type 2 diabetes. 42,43 The other major adipokine except adipocytokine is leptin. Leptin levels increase in obesity.…”
Section: Adipose Tissue and Hormones Secretionmentioning
confidence: 99%